2008
DOI: 10.1080/13625180701877712
|View full text |Cite
|
Sign up to set email alerts
|

Emergency obstetric care in Punjab, Pakistan: Improvement needed

Abstract: The study may be taken as a baseline for developing and improving the standards of services in Punjab province. It is vital to upgrade existing basic EmOC facilities and to ensure that staff skills be improved, facilities be better equipped in critical areas, and record keeping be improved. Hence to reduce maternal mortality, facilities for EmOC must exist, be accessible, offer quality services, and be utilized by patients with complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Zimba et al (2012) found that while Malawi has increased the percent of skilled deliveries, the majority of women and newborns with complications still lack access to essential services (37). Ali et al (2005) found the met need for Emergency Obstetric Care (EmOC) was only 9% in Pakistan [38]. A key next step is for countries to focus on and document scale-up so that progress can be measured (39).…”
Section: Resultsmentioning
confidence: 99%
“…Zimba et al (2012) found that while Malawi has increased the percent of skilled deliveries, the majority of women and newborns with complications still lack access to essential services (37). Ali et al (2005) found the met need for Emergency Obstetric Care (EmOC) was only 9% in Pakistan [38]. A key next step is for countries to focus on and document scale-up so that progress can be measured (39).…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding a wide network of facilities, a survey of public sector health facilities in Punjab showed that only 13% of facilities designed to provide basic emergency obstetric services were actually doing so [59]. The corresponding rate in North West Frontier Province (NWFP) is 10% [60].…”
Section: Introductionmentioning
confidence: 99%
“…The national cesarean rate in the rural population is reported as very low, 0.51%, and only 9.1% of the pregnant females have accessibility to emergency obstetric care. [34] In another study the overall cesarean rate in Pakistan's rural population was 9 per 100,1000 and in the developed countries the rate is 236 per 100,000 population. The rate of cesarean section is variable in developing and developed countries.…”
Section: Discussionmentioning
confidence: 97%
“…The crude birth rate is 30 per 100 and maternal mortality rate 500 per 100,000. [22,23,34] The rural communities do not have access to the minimal quality surgical care and cannot afford it either. [1,3,4] On paper the state has a system in place including basic health units (5171) and maternal and child centres (852) to provide primary healthcare services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation